1978
DOI: 10.1002/ange.19780900117
|View full text |Cite
|
Sign up to set email alerts
|

Neue Verbindungen aus 1,4‐Diaza‐1,3‐dienen und Eisencarbonylen: Hexacarbonyl(1,4‐diazadien)dieisen und substituierte 2(3H)‐Imidazolone

Abstract: Neuartige zweikernige Eisenkomplexe mit unsymmetrisch gebundenen 1,4‐Diaza‐1,3‐dienen (dad) entstehen auf den unten skizzierten Wegen. In Konkurrenz zur Bildung von (dad)Fe‐(CO)3 werden einige dad‐Liganden durch CO‐Insertion in Imidazolone umgewandelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The pattern of the absorptions is identical to that of [M 2 (CO) 6 (R-DAB/R-Pyca)] (M ϭ Fe, Ru, Os and FeRu). [6,[56][57][58][59] This strongly suggests that these complexes are isostructural, which is corroborated by the 1 H-and 13 C-NMR-spectroscopic data. The substituents on the α-imino ketone show only a marginal influence on the frequency of the CO absorption bands of complexes 7.…”
Section: Ir Uv/vis Spectroscopy and Elemental Analysissupporting
confidence: 65%
“…The pattern of the absorptions is identical to that of [M 2 (CO) 6 (R-DAB/R-Pyca)] (M ϭ Fe, Ru, Os and FeRu). [6,[56][57][58][59] This strongly suggests that these complexes are isostructural, which is corroborated by the 1 H-and 13 C-NMR-spectroscopic data. The substituents on the α-imino ketone show only a marginal influence on the frequency of the CO absorption bands of complexes 7.…”
Section: Ir Uv/vis Spectroscopy and Elemental Analysissupporting
confidence: 65%
“…The recent discovery by Brookhart and co-workers of Ni(II) and Pd(II) α-olefin polymerization catalysts containing bulky diimine ligands has stimulated renewed interest in the chemistry of 1,4-diazabutadiene (DAB) ligands and their complexes. Ligands of this type have been studied extensively in several different contexts. First, DAB ligands possess different possible modes of coordination as 2-, 4-, 6-, and even 8-electron donors in terminal, chelating, and bridging arrangements. These different modes of coordination in turn confer different reactivities on the complexed metal ions, as detailed in the review by van Koten and Vrieze . Second, as α-diimine ligands, DAB ligands have electronic structural similarities to the more extensively studied heteroaromatic chelating agents 2,2‘-bipyridine and 1,10-phenanthroline. , In 1973, for example, Miller and Dance showed that square-planar Ni(II) diimine dithiolate complexes containing 1,10-phenanthroline and the DAB ligand biactetyl bis(anil) (R = Ph; R‘ = Me) were spectroscopically similar with a common low-energy charge transfer-to-diimine absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, we have found that reaction of I with C O resulted in the formation of Ru,(CO),(R-DAB), where the R-DAB is now a a-N, p2-N', r12-CN' 6e donor, and only terminal carbonyls are present.2g As yet, no crystal structure of this compound has been obtained but we can assume the presence of a "normal" metalmetal internuclear distance, making reference to X-ray crystal structures of the isoelectronic home and heterodinuclear analogues [Fez( CO),( c-Hex-DAB) 34 and FeRu( CO),( i-Pr-DAB) 35] where the metal-metal distances are 2.597 and 2.660 A, respectively. This is in agreement with the LUMO (30 a') nature of I (see Figure 1 l), which is Ru-Ru' bonding but strongly antibonding between metals and the bridging CO and R-DAB ligands.…”
Section: Discussionmentioning
confidence: 99%